[PP.03.05] SERUM URIC ACID IS NOT ASSOCIATED WITH ALBUMINURIA IN PREHYPERTENSION AND NEWLY DIAGNOSED HYPERTENSION. (September 2016) - Karanovic, S.; Ivkovic, V.; Vrdoljak, A.; Dika, Z.; Domislovic, V.; Dapic, K.; Gallineo, L.; Ivandic, E.; Josipovic, J.; Vukovic, I.; Kos, J.; Laganovic, M.; et al.
Abstract : Objective: Elevated serum uric acid(SUA) even asymptomatic was found to be associated with blood pressure(BP), hypertension(HT), cardiovascular and chronic kidney disease. It was reported that xantin oxidase inhibitors(XOi) could in animals reverse glomerular hypertension and hypertrophy caused with hyperuricemia and in hyperuremic humans decrease microalbuminuria(MA). However, the question still remain whether elevated SUA is cause. marker, or just epiphenomen of renal impairment. Our aim was to analyze association of SUA with MA in prehypertensives(PHT) and newly diagnosed, untreated hypertensives(HT). Design and method: Out of 954 subjects enrolled in ENAH follow-up study, 371 (137 m, 234 w) were eligible for further analysis 100 with optimal, 72 with normal BP, 70 with PHT (high normal BP), and 129 with newly diagnosed HT. Exclusion criteria were treatment with antihypertensive drugs and XOi, diabetes, pregnancy, eGFR<60 ml/min, CV or cerebrovascular incident, chronic terminal diseases, dementia, immobility and missing data. BP was measured using Omron 6 device following the ESH guidelines. Fasting blood was analysed for SUA, glucose, lipids, serum creatinine, hsCRP. HOMA index was used to calculate insulin resistance and MDRD formula to estimate GFR. Albumin to creatinine ratio (ACR) was determined from the first morning spot urine. Results: In the whole group there is trend of lower ACR regarding SUA (1st vs. 2nd vs. 3rd tercile 5.78 vs. 5.11 vs. 4.65; p = 0.002). 78.3% subjects in the highest tertile of SUA were in the lowest tertile of ACR. Correlation of SUA and ACR was significantly negative (r = −0.21; p < 0.01), but after adjustment for age, gender, waist circumference, systolic BP, FBG, alpha1/CR significance was lost (beta = −0.09; p = 0.89). In the subgroup of PHT and HT SUA was also negatively correlated (r = −0.14; p = 0.02) but again the association was not significant after adjustment (beta = −0.10; p = 0.28). Trend of ACR across of SUA tertiles was the same as in the whole group (p = 0.02). Conclusions: In PHT and newly diagnosed, untreated HT, SUA is not associated with MA. Even more, our observation on negative association of SUA with MA might rise a provocative question whether in early phase of cardiorenal continuum elevated SUA, having antioxidative properties, might be even protective.